Ի.Ֆ. Շարիգինի «Երկրաչափություն 12» դասագրքի խնդիրների մեկի լուծման եղանակներ - Առաքելյան, Ռ.
В данной статье рассматривается решение одной из сложных задач из учебника И.Ф. Шарыгина для старшей школы «Геометрия 12» несколькими способами: нахождением объема тела по принципу Кавальери, с помощью формулы Ньютона-Симпсона и путем вычисления интеграла. Статья может служить в качестве методической помощи для учителей и учеников школ. In this article one of the difficult tasks from a textbook for high school "Geometry 12" by I.F.Sharygin was solved in several ways: finding of volume of a body by Cavalieri's principle; by means of Newton-Simpson's formula and by integral calculation. The article can be used as the methodical guide for school teachers and pupils.
Keywords: Մաթեմատիկայի դասավանդման մեթոդիկա